1992
DOI: 10.1530/jrf.0.0960735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low molecular weight oviductal factors on the development of mouse one-cell embryos in vitro

Abstract: The relationship between the oviduct and embryo development in the mouse was investigated and the period at which the influence of oviduct can be concerned in the development of mouse embryos in vitro was identified. In addition, the relative molecular weight of oviductal factors that promote embryo development was demonstrated. Mouse zygotes developed to the blastocyst stage when co-cultured with ampulla. The period of embryo co-culture significantly affected the further development of the embryos. Fewer one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
2

Year Published

1993
1993
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 24 publications
2
32
2
Order By: Relevance
“…In contrast, the benefits observed using MDBK cells were lost with Vero cells, suggesting either that some cell lines are unable to remove inhibitory factors from a poor medium such as B2 or that inhibiting factors are produced by certain cell lines. In addition, contrary to studies reporting the existence of a low molecular weight molecule which enhanced embryo development (Minami et al, 1992;Mermillod et al, 1993), no beneficial effect was consistently observed in any specific fraction tested in our work. This supports the idea that cells are responsive only to certain media and that feeder cells do not improve embryo development through specific factors secreted into the medium but only act by changing the base medium.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, the benefits observed using MDBK cells were lost with Vero cells, suggesting either that some cell lines are unable to remove inhibitory factors from a poor medium such as B2 or that inhibiting factors are produced by certain cell lines. In addition, contrary to studies reporting the existence of a low molecular weight molecule which enhanced embryo development (Minami et al, 1992;Mermillod et al, 1993), no beneficial effect was consistently observed in any specific fraction tested in our work. This supports the idea that cells are responsive only to certain media and that feeder cells do not improve embryo development through specific factors secreted into the medium but only act by changing the base medium.…”
Section: Discussioncontrasting
confidence: 99%
“…In the light of this, several studies have argued that a number of different cell lines may produce such a factor(s) Ouhibi et al, 1990;Minami et al, 1992;Bongso et al, 1993;Mermillod et al, 1993). In this study only B2 medium conditioned by MDBK cells improved embryo development, but no blastocyst formation was observed in B2 alone.…”
Section: Discussionmentioning
confidence: 56%
“…These granules seem to be those described in semi-thin sections as basophilic bodies which, at high magnification, appear surrounded by a limiting membrane and composed of fine, granular, electron-dense material (fig 9 and 11). These (Minami et al, 1992) and more recently in human oviductal cells (Liu et al, 1995 (Takahashi and First, 1992), some toxic components of M-199 as hypoxanthine (Loutradis et al, 1987), phosphate (Pinyopummintr and Bavister, 1991) and superoxide radicals (Noda et al, 1991). Low molecular weight antioxidants, as taurine (Tiffin et al, 1991) and gluthatione (Legge and Sellens, 1991), could also have been secreted into the medium.…”
Section: Methodsmentioning
confidence: 99%
“…Development of one-cell embryos to blastocyst was sig nificantly enhanced by culture in conditioned medium [19], suggesting that some factors in conditioned media are effective for embryonic development. The existence of oviduct-specific glycoproteins has been demonstrated in mice [20], hamsters [21], rabbits [22], sheep [23,24], baboons [25] and cattle [26], but the biological functions of these molecules remain to be clarified.…”
Section: Mouse Embryo Culture In Explanted Mouse Oviductsmentioning
confidence: 99%